Educational Ministry Field: Where and To Whom Is Education Directed - Gobai, Mika (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The message of Christian education represents a theological and educational mandate rooted in the Great Commission and the concept of missio Dei, which positions the entire world and all humanity as the field of God-centered education. However, previous studies have tended to separate the geographical and relational dimensions of educational engagement, resulting in the absence of an integrative educational and theological framework, particularly within the context of Indonesia’s pluralistic society. This study aims to construct an integrative theological framework regarding the field of ministry of the message of Christ based on spatial (where) and relational (to whom) dimensions. The method used is a literature review with a content analysis approach and theological-conceptual synthesis of biblical sources and contemporary theological and missiological literature. The results of the study show that the field of gospel ministry covers the whole world, local communities, and daily life, while the goal of the ministry includes all human beings, especially marginalized communities and pluralistic societies. Evangelism is realized holistically through living witness, acts of love, and verbal preaching. In conclusion, the field of evangelical ministry is universal, relational, and existential, and affirms that every believer actively participates in the missio Dei through a transformative contextual life in a pluralistic society.